Gerakan Siswa Mengajar (GSM) Implementasi Metode Tutor Sebaya di SMPN 1 Mejayan Kabupaten Madiun - Mustofa Aji Prayitno (Al-Riwayah : Jurnal Kependidikan, 2021)
This study aims to determine the stages of implementing the peer tutoring method in the learning process and the implementation of the Gerakan Siswa Mengajar (GSM) at SMP Negeri 1 Mejayan, Madiun Regency. Data collection techniques used in this study using triangulation techniques. Data and sources of research data were obtained through interviews with resource persons involved and related in the implementation of peer tutoring learning methods, namely coaches, teachers, and class IX students of SMP Negeri 1 Mejayan Madiun Regency, observing the implementation of the Gerakan Siswa Mengajar (GSM), documentation and literature as a source of supporting data. Analysis of research data was carried out in three stages, namely the stage of data reduction (data reduction), data presentation (data display), and drawing conclusions (conclusion drawing). The data reduction stage of this research was carried out by focusing on the research data and summarizing the main points of the research, the stage of presenting the data in the form of narratives and explanations, and the stage of drawing conclusions through drawing conclusions and conclusions from the research results from existing data. The results showed that: (1) The stages of implementing the peer tutoring method in the GSM program (Gerakan Siswa Mengajar) at SMP Negeri 1 Mejayan Madiun Regency included three stages, namely the preparation stage, the implementation stage, and the evaluation stage. (2) In its implementation, the GSM (Gerakan Siswa Mengajar) program at SMP Negeri 1 Mejayan applies a creative, innovative and fun system, the aim is to optimize the active role of students in the learning process, as an effort to increase student test scores, especially in the graduation exam and national exam (UN), optimizing academic potential and character values ​​in students, as well as realizing a creative, innovative, and fun learning process.